CFD Investigation of Non‐Condensable Gases in Vacuum and Non‐Vacuum Steam Sterilizers. Issue 4 (21st January 2019) - Feurhuber, Manuel; Magno, Marino; Miranda, Marco; Prieler, René; Hochenauer, Christoph
Abstract: Steam sterilization processes rely on high heat transfer rates from the steam to the medical devices. To guarantee this, all non‐condensable gases (NCGs) must be removed from the steam sterilizer before sterilization. The ratios and distribution of the NCGs in the pre‐sterilization phases of both a vacuum and a non‐vacuum steam sterilizer are investigated. Two CFD models for simulation of the NCGs in the sterilizers were developed and validated by the measurements of a pressure sensor and eight thermocouples inside the steam sterilizer. Furthermore, a novel method was developed to calculate the real ratio of NCGs based on the standard measurement (EN 13060). The results show that the NCGs ratio defined in the EN 13060 did not accurately represent the real ratios of the NCGs. Abstract : Prior to sterilization of medical devices, non‐condensable gases (NCGs) must be removed from the steam sterilizer to ensure high heat transfer rates. The NCGs in a vacuum and a non‐vacuum steam sterilizer were simulated by CFD models and a novel method to calculate the real ratio of NCGs based on the standard measurement (EN 13060) was developed.